Combined Transphyseal and Lateral Extra-articular Pediatric Anterior Cruciate Ligament Reconstruction: A Novel Technique to Reduce ACL Reinjury While Allowing for Growth. Issue 14 (December 2019) - Wilson, Philip L.; Wyatt, Charles W.; Wagner, K. John; Boes, Nathan; Sabatino, Meagan J.; Ellis, Henry B.
Background: Treatment of anterior cruciate ligament (ACL) injuries in the adolescent population continues to be complicated by an unacceptably high rate of secondary ACL injury. Purpose: To describe the failure rate and outcomes after a hybrid pediatric ACL reconstruction (ACLR) employing transphyseal hamstring (TPH) autograft combined with an extra-articular technique using an iliotibial band (ITB) autograft. Study Design: Case series; Level of evidence, 4. Methods: Consecutive patients undergoing combined TPH-ITB ACLR between January 2012 and April 2017 with a minimum 2-year follow-up were reviewed. With the goal of decreasing ACL graft injury in this high-risk group, this technique employed anteromedial portal drilling for TPH with an extraosseous femoral ITB technique and intra-articular TPH-ITB grafts fixed within the tibial bone tunnel. Demographics, bone age, standing alignment radiograph for growth and mechanical axis grade, return to sport, graft failure, and patient-reported outcome measures were analyzed. Results: A total of 61 knees in 60 adolescents underwent the combined TPH-ITB ACLR, with 57 knees (93.4%) meeting inclusion criteria with a mean follow-up of 38.5 months (range, 24-78 months). Only 3 of 57 knees (5.3%) sustained ACL reinjury. The mean age was 13.0 years (range, 11-16 years) with 36 male patients (mean bone age, 14.2 years) and 21 female patients (mean bone age, 13.3 years), and 91% of patients (52 of 57) returned to sport. Participants demonstrated a high functional level at final follow-up, with a mean score of 91.2 (range, 46.7-100) on the Pediatric International Knee Documentation Committee (Pedi-IKDC) Subjective Knee Evaluation Form and mean score of 22.4 (range, 4-30) on the Pediatric Functional Activity Brief Scale (Pedi-FABS). To critically assess growth, a cohort with ≥18 months of growth remaining at surgery was evaluated at maturity. No difference was seen in mean operative and nonoperative leg growth (49.7 mm and 49.8 mm). Although no family reported cosmetic or functional alignment or length concerns, 1 of 18 (5.5%) had a final limb length discrepancy >10 mm (12 mm) and a perioperative alignment difference (0-Grade II valgus). Conclusion: Combined TPH-ITB ACLR in adolescents resulted in high activity levels (Pedi-FABS, 22.4; median, 25) and a low (5.3%) graft failure rate at a mean 38.5 months.